2004
DOI: 10.1093/ajcn/80.5.1270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral vitamin E and β-carotene supplementation on ultraviolet radiation–induced oxidative stress in human skin

Abstract: Vitamin E or beta-carotene supplementation had no effect on skin sensitivity to UVR. Although vitamin E supplements significantly reduced the skin malondialdehyde concentration, neither supplement affected other measures of UVR-induced oxidative stress in human skin, which suggested no photoprotection of supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 36 publications
1
55
0
2
Order By: Relevance
“…Chow et al [17] reported that a 4-week intake of green tea polyphenols (800 mg/ day of epigallocatechin gallate) did not affect the MED of the subjects. Similarly, McArdle et al [18] found that supplementation with vitamin E or ␤ -carotene did not affect the skin's sensitivity to UV light.…”
Section: Discussionmentioning
confidence: 95%
“…Chow et al [17] reported that a 4-week intake of green tea polyphenols (800 mg/ day of epigallocatechin gallate) did not affect the MED of the subjects. Similarly, McArdle et al [18] found that supplementation with vitamin E or ␤ -carotene did not affect the skin's sensitivity to UV light.…”
Section: Discussionmentioning
confidence: 95%
“…Derg. 40(1): [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]2016 Şen 39 fotohasarın şiddetiyle orantılıdır. Tip IV kollagen dermoepidermal bileşkedeki temel kollajen olup mekanik etkileşim için büyük önem taşımaktadır.…”
Section: Yaşlanma Sonucu Deride Görülen Değişikliklerunclassified
“…Also, there are a few papers that indicated the absence of a positive action of supplemented antioxidants on skin health [112,119,138,149,151] .…”
Section: Systemic Application Of Synthetic and Extracted Antioxidantsmentioning
confidence: 99%